Electronic Building and Properties of Aluminum Nitride Irradiated with Ions; 7 International conference on modification of materials with particle beams and plasma flows - Kabyshev A. V. Alexander Vasilievich (Fundamentals of modification processes, 2004)
Title from the title-page.